2021
DOI: 10.4103/jfmpc.jfmpc_2416_20
|View full text |Cite
|
Sign up to set email alerts
|

Perception of safety from workplace violence affects job satisfaction among doctors practicing modern medicine in India

Abstract: Background: Doctors are often been judged negatively as a consequence of high expectation and demand from their job and face violence at workplace. Continuous worry of facing aggression at workplace may seriously affect job satisfaction and intention to job turnover. However, the association between workplace safety and job satisfaction had not been studied earlier in India. Methods: A cross-sectional survey was conducted among doctors from November 2019 to April 2020 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The present study has found no other instance, in India, where healthcare professionals have been studied with regards to enrichment or facilitation which further reinforces raison de'etre of the present article. Job and family satisfaction has been studied among Indian doctors mainly along psycho-social dimensions including burnout (Srivastava et al ., 2019), stress (Bhatia, 2019), workplace violence (Ahamed et al ., 2021) and psychological distress (Atif et al ., 2018), among others.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The present study has found no other instance, in India, where healthcare professionals have been studied with regards to enrichment or facilitation which further reinforces raison de'etre of the present article. Job and family satisfaction has been studied among Indian doctors mainly along psycho-social dimensions including burnout (Srivastava et al ., 2019), stress (Bhatia, 2019), workplace violence (Ahamed et al ., 2021) and psychological distress (Atif et al ., 2018), among others.…”
Section: Hypotheses Developmentmentioning
confidence: 99%